Frequency of Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency in Neonates with Jaundice - Hadi, Noor Ul; Tul Muntaha, Sidra; Hafeez, Muhammad; Ahmad, Rafiq; Hassan, Farhan; Afzal, Mian Mansoor (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the frequency of glucose-6-phosphate dehydrogenase deficiency among neonates presenting with jaundice. Methods: It was a Descriptive cross-sectional study using non-probability consecutive sampling conducted in the Department of Pediatrics, Saidu Group of Teaching Hospitals, Saidu Medical College, Swat, Pakistan, from 22nd July 2023 to 22nd January 2024. A total of 130 neonates aged 1–28 days with clinical jaundice were enrolled. Baseline demographic and clinical data were collected. Laboratory evaluation included serum bilirubin, hemoglobin, reticulocyte count, and glucose-6-phosphate dehydrogenase activity by decolorization test. A decolorization time exceeding 60 minutes was considered diagnostic for enzyme deficiency. Results: Of the 130 neonates, 70% were aged 1–14 days, and 30% were 15–28 days. Term neonates constituted 68%, while 32% were preterm. Male-to-female ratio was 1.3:1 (58% vs. 42%). Glucose-6-phosphate dehydrogenase deficiency was detected in 10% of neonates with significantly higher frequency in males (16%) compared to females (2%) (p=0.0077). Conclusion: Glucose-6-phosphate dehydrogenase deficiency was observed in 10% of neonates with jaundice, with a marked male predominance. Early screening is essential to prevent complications such as severe hyperbilirubinemia and kernicterus in high-risk populations. Keywords: Anemia, Hemolytic; Glucose-6-Phosphate Dehydrogenase Deficiency; Hyperbilirubinemia, Neonatal; Infant, Newborn; Jaundice.